Indeks Massa Tubuh Menurut Umur sebagai Indikator Persen Lemak Tubuh pada Remaja - rosidi, ali (Jurnal Gizi, 2018)
Health impact which caused by overnutrition is related to excess in body fat. Thus, nutritional status monitoring in adolescent is crucial because the prevelance of overnutrition in adolescent increased per years. Body Mass Index per age (BMI/A) is easy, simple, and generally used to determine nutritional status, but incapable to measure overnutrition related excess body fat precisely. Body fat percentage is used to determine overnutrition but special equipment and capability are required. The purpose of the study are to analyze correlation between BMI/A and body fat percentage and verify BMI/A’s sensitivity-specificity as body fat percentage’s indicator. In this cross sectional study, 82 adolescents from SMAN 47 Jakarta are chosen to participate by simple random sampling. Anthropometric instrument that used are microtoise, spring scales, and bioelectrical impedance analysis (BIA). There is a significant correlation with a strong value between BMI/A and percent body fat (r=0,814; p=0,000). BMI/A as percent body fat’s indicator has low sensitivity and high specificity (Se= 55,17%; Sp= 94,34%). Eventhough there is strong correlation, BMI/A is less sensitive as percent body fat’s indicator to determine nutritional status in adolescent, thus body fat measurement is needed to validate value of BMI/A measurement.